2022
DOI: 10.3390/fermentation8030129
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable and Eco-Friendly Conversions of Olive Mill Wastewater-Based Media by Pleurotus pulmonarius Cultures

Abstract: Pleurotus pulmonarius mushroom was cultivated on liquid cultures with olive mill wastewaters (OMWs) of initial phenolic compound concentrations of 0 (control), 1, 2 and 3 g/L and glucose at initial concentrations of 40 and 60 g/L. The ability of the fungus to grow on media containing toxic compounds enriched with glucose was assessed through biomass production, glucose consumption, polysaccharide (IPS) accumulation and total cellular lipids biosynthesis, while the total phenolic compounds (TPC) and antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…Our study presents a higher dephenolization rate, and from a study of P. ostreatus using grape pomace as a substrate, its value reached only 68%, while the laccase production maximum value was 4447 U/g of substrate, and the biomass reached a value of 0.42 ± 0.01 g/g substrate [42]. Our values for dephenolization and decolorization were close to that published by Diamantis et al for Pleurotus pulmonarius in Olive mill wastewater, with the observed values ranging from 87% to 95% for dephenolization and from 70% to 85% for decolorization [43]. Focusing on laccase production, our study revealed higher laccase production levels in comparison with other studies for Pleurotus ostreatus involving cultivation on 20 g/L tomato pomace and 1 g/L ammonium sulfate (0.147 Units/mL), cultivation on 20 g/L glucose and 5 g/L peanut shell (5 Units/mL), cultivation on 20 g/L glucose and 5 g/L bagasse (15 Units/mL), cultivation on 20 g/L glucose and 5 g/L tea leaflets (30 Units/mL), and cultivation on 20 g/L glucose and 5 g/L orange peel (45 Units/mL) [14,44].…”
Section: Thermodynamicssupporting
confidence: 87%
“…Our study presents a higher dephenolization rate, and from a study of P. ostreatus using grape pomace as a substrate, its value reached only 68%, while the laccase production maximum value was 4447 U/g of substrate, and the biomass reached a value of 0.42 ± 0.01 g/g substrate [42]. Our values for dephenolization and decolorization were close to that published by Diamantis et al for Pleurotus pulmonarius in Olive mill wastewater, with the observed values ranging from 87% to 95% for dephenolization and from 70% to 85% for decolorization [43]. Focusing on laccase production, our study revealed higher laccase production levels in comparison with other studies for Pleurotus ostreatus involving cultivation on 20 g/L tomato pomace and 1 g/L ammonium sulfate (0.147 Units/mL), cultivation on 20 g/L glucose and 5 g/L peanut shell (5 Units/mL), cultivation on 20 g/L glucose and 5 g/L bagasse (15 Units/mL), cultivation on 20 g/L glucose and 5 g/L tea leaflets (30 Units/mL), and cultivation on 20 g/L glucose and 5 g/L orange peel (45 Units/mL) [14,44].…”
Section: Thermodynamicssupporting
confidence: 87%
“…The metabolism of many macrofungi has been studied in synthetic media with various carbon and nitrogen sources to determine growth patterns and their productivity [21,22]. Current research indicates that satisfying quantities of macrofungi mycelial biomass can be produced in liquid cultures using agro-industrial side-streams as the sole carbon source [23][24][25][26][27]. Submerged cultivation of macrofungi is an efficient, reproducible, and potentially scalable method to produce fungal biomass and metabolites (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in the research related to the biotechnological valorization of OMWs indicate that these liquid streams should be considered as a fermentation medium to valorize rather than a waste to discharge, being as both a process water and a potential liquid substrate for various fermentation processes [ 11 , 20 , 21 , 22 , 23 ]. In several cases, OMWs have been employed to “dilute” “concentrated” residues and waste streams like molasses and crude glycerol [ 14 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In several cases, OMWs have been employed to “dilute” “concentrated” residues and waste streams like molasses and crude glycerol [ 14 , 24 , 25 ]. It is evident that a prerequisite for the successful accomplishment of the mentioned bioprocess would be that the implicated microorganisms would withstand the (potentially elevated concentrations of the) phenolic compounds found in the OMW-based media [ 14 , 18 , 20 , 21 , 23 , 24 , 26 ] while of significant interest, would be the simultaneous detoxification ( viz . dephenolization and decolorization) of the OMW-based media, together with the production of added-value metabolites [ 14 , 18 , 23 , 24 , 26 ].…”
Section: Introductionmentioning
confidence: 99%